Assessing insulin resistance: the triglyceride-glucose index as a predictor of survival in nasopharyngeal carcinoma - Hua, Xin; Xu, Fei; Lin, Xu-Xin; Lin, Yong-Miao; Long, Zhi-Qing; Wang, Si-Fen; Duan, Fang-Fang; Zhang, Chao; Huang, Xin; Xia, Wen; Li, Wen-Chao; Chen, Ao-Qiang; et al. (Frontiers in Physiology, 2026)
BackgroundThe triglyceride-glucose (TyG) index, a simple marker of insulin resistance, has shown prognostic value in various malignancies. However, its predictive utility for survival in nasopharyngeal carcinoma (NPC) patients remains largely unexamined. This study aimed to assess the prognostic value of the TyG index and to develop novel predictive models for survival outcomes in NPC.MethodsWe retrospectively analyzed 833 NPC patients treated with concurrent chemoradiotherapy (CCRT). All patients were staged according to the 8th edition of the American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) TNM staging system. The TyG index was calculated as ln (fasting triglycerides × fasting glucose). Primary and secondary endpoints were overall survival (OS), locoregional recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS), respectively. We utilized univariate and multivariate Cox proportional hazards models to identify independent prognostic factors and subsequently constructed and validated nomograms.ResultsA low TyG index was significantly associated with better survival outcomes, serving as an independent predictor for OS (hazard ratio [HR] = 0.534; P = 0.007), LRFS (HR = 0.423; P < 0.001), and DMFS (HR = 0.575; P = 0.010) in multivariate analysis. The newly developed nomograms demonstrated favorable discriminative performance, significantly outperforming the conventional TNM staging system (concordance index [C-index] for OS: 0.722 vs. 0.634).ConclusionThe TyG index is a readily available, powerful prognostic biomarker for NPC patients. Incorporating the TyG index into prognostic nomograms offers a superior tool for individualized risk stratification and treatment planning, representing a valuable advancement over traditional staging systems.